ANALISIS KRIMINOLOGI TINDAK PIDANA PENIPUAN OLEH ANGGOTA POLRI DI POLRES SOLOK SELATAN - Henwel, Henwel (LPPM Universitas Ekasakti Padang, 2019)
In committing a crime of fraud, of course, a perpetrator must have tactics or methods used in carrying out the action, because this is done by the deceiver so that his goal to cheat can be achieved. Associated with fraudulent crimes that occur in South Solok can not be separated from various factors that encourage the perpetrators to do these actions, ranging from economic, social motives and may even be driven by evil instincts that exist in my servants. Every criminal act committed is closely related to the character and character of a criminal.